1987
DOI: 10.1051/rnd:19870705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wheat bran on exocrine pancreas secretion in the pig

Abstract: Summary. The aim of this study was to determine the effect of wheat bran consumption on exocrine pancreas The results show that wheat bran intake induced an increase in the volume (+ 115 %) and protein output (+ 36 %) of the pancreatic juice secreted in a 24-hour period, whereas protein concentration decreased. All enzyme activities were enhanced by wheat bran. The plasma levels of secretin, VIP, somatostatin and PP were higher in the experimental than in the control group. On the contrary, plasma CCK levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 16 publications
(22 reference statements)
2
22
0
Order By: Relevance
“…In the pig, it has been shown that the level of fibre in the diet affects the volume of pancreatic juice secreted (LANGLOIS et al 1987) and the total output of protein and enzyme activity are mainly regulated by the intake of protein, carbohydrate and fat (BRANNON 1990). The present study is thus in agreement with these findings and also demonstrates the dietary effects on the bicarbonate-chloride exchange mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…In the pig, it has been shown that the level of fibre in the diet affects the volume of pancreatic juice secreted (LANGLOIS et al 1987) and the total output of protein and enzyme activity are mainly regulated by the intake of protein, carbohydrate and fat (BRANNON 1990). The present study is thus in agreement with these findings and also demonstrates the dietary effects on the bicarbonate-chloride exchange mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…As far as the pancreatic secretion was concerned, the daily volume of juice secreted was in the range of values obtained by others (Partridge et al, 1982;Zebrowska et al, 1983;Corring et al, 1986;Langlois et al, 1987). The pancreatic juice flow rate was shown to be affected by the concentration of the diet (ie, liquid, solid, semisynthetic or natural), being lower with a semi-synthetic diet (Partridge et al, 1982;Zebrowska et al, 1983).…”
Section: Animals and Dietmentioning
confidence: 56%
“…It was lower in animals fed a semisynthetic diet than in animals given a normal diet with similar amounts of nutrients (1.9 g vs 2.1 g according to Zebrowska et al, 1983; 1.1 g vs 1.5 g according to Partridge et al, 1982). The pancreatic endogenous total nitrogen production was 2.1 g per day in the pig fed heated soyabean (Corring et al, 1986) or 2.3 g per day when the diet contained wheat (Langlois et al, 1987). Furthermore, the present study shows that the amount of pancreatic nitrogen increased after meal intake, as reported earlier (Corring, 1980).…”
Section: Nitrogen Concentration and Productionmentioning
confidence: 93%
“…Similar results were obtained in this experiment and treatment three and five improved crude protein utilization compared with the control. It is possible that the inclusion of WB in diets might have enhanced the secretion of digestive enzyme and juices that are beneficial to protein digestion (Langlois et al, 1987;Valette et al, 1989). Research indicated that microbial phytase increased the dietary nitrogen retention (Ketaren et al, 1993;Mroz et al, 1994).…”
Section: Discussionmentioning
confidence: 99%